Compliance of MSME Taxpayers Using the Shopee Marketplace Platform in Banten Province: Relevance to Tax Policy in Indonesia - Indana Afiyah (Primanomics : Jurnal Ekonomi & Bisnis, 2026)
This study aims to test and analyze the influence of Income Turnover, Understanding of Government Regulation No. 23 of 2018 and Government Policies on Tax Incentives on the Compliance of MSME Taxpayers Using the Shopee Marketplace Platform. The population in this study is Individual Taxpayers e-commerce actors  in Banten Province who market their products through  the Shopee Marketplace online platform, and the sample used is 97 entrepreneurs who have stores on the Shopee Marketplace. This research is quantitative. The type of data in this study is primary, and the source of data is from the questionnaire. The results of the study show that Income Turnover, Understanding of Government Regulation No. 23 of 2018 and Government Policy on Tax Incentives have a simultaneous effect on the Compliance of MSME Taxpayers Using  the Shopee Marketplace Platform. The understanding of Government Regulation No. 23 of 2018 partially has a significant effect on the compliance of MSME Taxpayers who use  the Shopee Marketplace Platform. Meanwhile, Income Turnover and Government Policies on Tax Incentives have no effect on the Compliance of MSME Taxpayers Using the Shopee Marketplace Platform.